2018
DOI: 10.1080/07315724.2018.1461147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Coffee Consumption on Resting Energy Expenditure, Blood Pressure, and Body Temperature in Healthy Women: A Pilot Study

Abstract: The results of this study showed that 6 mg caffeine/kg (lean body mass) intake among women changed body temperature and blood pressure values and liquid balance depending on the usual dietary coffee intake. In addition, chlorogenic acid is also correlated with REE values besides green coffee caffeine. Key teaching points • There are several findings, and chlorogenic acid may have antihypertensive effects. • There is a significant correlation between green coffee chlorogenic acid amount and REE. • Intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The pilot study did not compare effects of a placebo or other sources of caffeine. However, the metabolic changes were compared between baseline/before and after ingestion when evaluating the effects of green coffee [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pilot study did not compare effects of a placebo or other sources of caffeine. However, the metabolic changes were compared between baseline/before and after ingestion when evaluating the effects of green coffee [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorogenic acid has been reported to have beneficial effects against obesity and other dysmetabolic disorders, as well as playing a favorable role in energetic metabolism in both human and animal studies [59,60]. In a pilot study, the consumption of 1 cup of green coffee (containing 6 mg caffeine per kg of lean body mass, about 215-280 mg) determined an increase of REE by 6.4% at 30 min and 2.2% at 180 min, with a positive correlation between the chlorogenic acid assumed and the REE values at 30 min [61].…”
Section: Green Coffee Available Evidencementioning
confidence: 99%
“…Although propolis has been highlighted for its ability to strengthen the immune system through the COVID-19 process, it is also responsible for a wide range of antiviral, anti-inflammatory, and antioxidant activities due to polyphenols in its composition such as catechins, caffeic acid, Artepillin C, quercetin, and chlorogenic acid [ 15 17 ]. Various research has demonstrated that phenolic components such as catechin, quercetin, and chlorogenic acid have been associated to energy expenditure and lower body mass index (BMI) [ 18 – 22 ]. Polyphenols may have a role in body weight management by activating-oxidation, inducing satiety, increasing energy expenditure, promoting adipocyte death, and stimulating lipolysis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%